The Analysis of Training Factors and Motivational Factors to Improve the Performance of Employees of PT. Bank Victoria (PT.BA) - Novita, Yohana; Tobing, Suzanna Josephine L.; Kennedy, Posma Sariguna Johnson (Fundamental Management Journal, 2018)
This study aims to analyze (1) whether there was a relationship between training factors and the performance of employees of PT. Bank Victoria International Tbk (PT.BV); (2) is there a relationship between motivational factors and the performance of employees of PT. Bank Victoria. The next results in this study are (1) there is a relationship between training factors and the performance of employees of PT. Bank Victoria. This is indicated by the significance value smaller than 0.05 is (0,000) <(0.005). With Spearman rank correlation coefficient of 0.481. (2) there is a relationship between motivational factors and the performance of employees of PT. Bank Victoria. This is indicated by the significance value smaller than 0.05 is (0,000) < (0.005). With Spearman rank correlation coefficient of 0.453. Keyword : training factors, motivation factors, employee performance